Vigilância e controle: atuação do SNI sobre a comunidade acadêmica da Universidade Federal da Paraíba (1964–1985) - Dias, Elissandra Maria Costa (2021)
This work aims to understand how the surveillance exercised over the Universidade Federal da Paraíba (UFPB) occurred through the Serviço Nacional de Informações (SNI) and other information agencies (OI), especially the UFPB Assessoria de Segurança e Informações (ASI/ UFPB), during the Military Dictatorship (1964 - 1985). Therefore, this research uses, as a primary source, the documents that are part of the SNI Fund – Agência Recife and the documents of the ASI/UFPB, which in 2016 was delivered to the Comissão da Verdade e Preservação de Memória do Estado da Paraíba (CEVPM-PB) and today it is under the custody of the Paraíba Democracy Memorial, located at the Fundação Casa de José Américo. The documents in question were produced during the permanence of authoritarian governments, and, therefore, are characterized as “sensitive documents”, as they were inserted in the logic of production that served the repression. (BAUER; GERTZ, 2013, p. 178). In order to cross the information contained in the official documentation and to better understand the processes that constitute the analyzed temporality, we will use some of the testimonies of UFPB members, which were granted in public hearings to CEVPM-PB. Regarding the theoretical paths, this research is inserted in the field of new political history and, along with that, it employs the concept of "political culture", as it is intended to identify the ways of proceeding of the information agencies in the UFPB, through the knowledge of who were being watched and which political currents were under surveillance. We aim, in this way, to demonstrate how the dictatorship, through agencies at its service, both at UFPB and at other universities, persecuted, watched and censored people and ideas. For a more solid understanding, we have included this research in the Line: History and Regionalities of the Programa de Pós-Graduação em História of Universidade Federal da Paraíba (PPGH-UFPB).